Oxytetracycline residues in bovine muscles, liver and kidney tissues from selected slaughter facilities in South Western Uganda - Kebirungi, Pheonah; Nyombi, Anthony; Omara, Timothy; Adaku, Christopher; Ntambi, Emmanuel (Bulletin of the National Research Centre, 2020)
Background: Due to high disease burden and poor animal health services in Uganda, administration of antimicrobials particularly oxytetracycline (OTC) is often done by farm owners and workers without any prescription. This results in misuse of OTC with consequent high chances of antibiotic residues and antimicrobial resistance hence posing public health threat. The degree of public health threat from OTC use is not well established due to limited published data on antibiotic residues and usage in livestock production in Uganda. This study comparatively determined OTC residue levels in 318 samples of bovine muscles, liver and kidney tissues from Kiruhura, Mbarara and Ntungamo districts of South Western Uganda during dry and wet seasons. Results: The results revealed that the overall OTC residues positivity levels was 74.84% while the district wise rates were 56.88%, 84% and 84.52% for Kiruhura, Mbarara and Ntungamo, respectively. The mean OTC residue levels in bovine muscles, liver and kidney tissues were above the recommended maximum residue limits of 200, 600 and 1200 μg/kg, respectively as established by FAO/WHO. Of the collected samples, 72.41% (236/318) had OTC residues in concentrations above the recommended maximum residue limits. Wilcoxon signed rank test results showed that change in the seasons did not cause any significant changes in the liver OTC residue levels for all the districts, though this was significant for muscles from Kiruhura and Mbarara districts. Unacceptably high OTC levels were found in the muscles, liver and some kidney samples: Kiruhura muscles and liver samples had mean OTC concentrations of 1094 ± 378 μg/kg and 967 ± 198 μg/kg; Mbarara muscles, liver and kidney samples had mean OTC mean concentrations of 668 ± 163 μg/kg, 3778 ± 1140 μg/kg and 12,576 ± 1630 μg/kg, respectively while Ntungamo samples had mean OTC concentrations of 586 ± 123 μg/kg and 5194 ± 1463 μg/kg in muscle and liver tissues. Conclusions: The results of this study indicated that there are unacceptably high OTC residue levels in bovine tissues consumed in South Western Uganda. This poses a public and veterinary health threat to consumers of these bovine tissues.
Keywords: Oxytetracycline; Antimicrobial residues; Uganda; Cattle corridor; Antibiotic misuse